Primary students’ participation in school based mathematical reasoning practices: Coordinating reciprocal teaching and systemic functional linguistics to support reasoning in the Swedish context - Segerby, Cecilia; Chronaki, Anna (EDeR. Educational Design Research, 2018)
The foreign language (FL) classroom can be an anxious environ- ment where students feel uncomfortable having to communicate in a language in which they feel inadequate and have little practice. Low self-efficacy in skill-specific tasks is oftentimes the culprit. While there are a number of factors involved in successful language learning, this study examines how practice affects students’ sense of self-efficacy in the foreign language classroom. Using self-efficacy theory and design-based research, this qualitative study ‘flipped’ the classroom to focus on student input and output practice in class with grammar instruction video-recorded for homework. Data were recursively collected and analyzed from ten courses over three semesters. Classroom observations and reflection were triangulated with interviews and focus groups. Findings suggest that practice and self-efficacy in the FL classroom are indeed linked and that other factors such as peer familiarity and grading also play a role. The paper concludes with implications for language learning and teaching.